Literature-Based Strategies for Clinical Fellow Mentorship - Freeman, Max R.; Walden, Patrick R. (Seminars in Speech and Language, 2020)
In the field of communication sciences and disorders, some research and guidance exist on clinical fellowship supervision for the mentor; however, there is a dearth of literature on clinical fellowship supervision from the perspective of the clinical fellow. This article begins with why the clinical fellowship experience is necessary, and then discusses clinical fellow and mentor expectations and responsibilities, clinical fellow independence, mentor qualities, and issues related to the provision of feedback. The overall goal is to enhance clinical fellow mentors' knowledge base on the clinical fellowship experience through review of current literature on supervision and mentorship.
Keywords: clinical fellowship; supervision; mentorship